2014
DOI: 10.1080/00038628.2014.939132
|View full text |Cite
|
Sign up to set email alerts
|

Thermal comfort and practicality: separate winter and summer rooms in Iranian traditional houses

Abstract: Traditional houses in hot dry regions of Iran provide conditions in which the inhabitants could cope with the severe climate. Previous research shows that these vernacular houses work as a complex passive cooling system that modifies the internal climatic conditions. This complex modifying system has various components or sub-systems of which one is the existence of separate seasonal rooms in the house. This study focuses on the use and performance of seasonal rooms. It used a range of different methods includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 9 publications
0
19
0
Order By: Relevance
“…Iran is a large country with a population consisting of several tribes, and although there are differences, there are many shared behavioural traits both within Iran and with other Middle Eastern countries (Memarian and Brown, 2006). Traditionally, spaces within Iranian houses are multi-use, meaning their usage and furnishing change both over the day and with the seasons (Foruzanmehr, 2014).…”
Section: Sharing Space In Everyday Life In Iranmentioning
confidence: 99%
See 1 more Smart Citation
“…Iran is a large country with a population consisting of several tribes, and although there are differences, there are many shared behavioural traits both within Iran and with other Middle Eastern countries (Memarian and Brown, 2006). Traditionally, spaces within Iranian houses are multi-use, meaning their usage and furnishing change both over the day and with the seasons (Foruzanmehr, 2014).…”
Section: Sharing Space In Everyday Life In Iranmentioning
confidence: 99%
“…"Poshti" form a good JFM 14,2 replacement for couches, as they let more guests be entertained in a small room and can easily be picked up and stored when not needed. Similarly, Iranian people traditionally slept on the ground at night on mats, which in the morning were folded and stored in spaces designed for this (Foruzanmehr, 2014). Although recently these habits have changed with modernisation, many people still like to live, eat and sleep as in the past with this flexible use of space.…”
Section: Sharing Space In Everyday Life In Iranmentioning
confidence: 99%
“…Keshtkaran (2011) [15] presented data to prove the harmony between climate and architecture of Yazd. Foruzanmehr surveyed different elements of Yazd's vernacular architecture, their performance and role in dwellers' lives through several studies [8,12,[16][17][18][19] and concluded that vernacular houses provide a more comfortable living environment compared to modern apartments in most cases. Khalili and Amindeldar (2014) [13] studied the logic and performance of traditional solutions in low-E vernacular buildings of hot-arid regions in Iran and concluded that these buildings provide a sustainable environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sash windows are operable full‐wall windows used for central rooms (Foruzanmehr, ), dispersing light deeply into them. By opening ascending windows a large amount of daylight is received, and by closing them severe light is prevented (Figure ).…”
Section: Data Collection and Analysismentioning
confidence: 99%